Etiologia da mastite bovina, em programa de controle - Salina, Anelise [UNESP]; Joaquim, Samea Fernandes [UNESP]; Langoni, Helio [UNESP] (GN1 Sistemas e Publicacoes, 2014)
Mastitis is a major health problem in a dairy property. It is a multifactorial infectious process. This is a study of the dynamic of infection in dairy herd, with monthly visits for a period of one year to evaluate the prevalence of clinical and subclinical cases, with the aim of establishing the control program. The results obtained to date with regard the etiology of mastitis subclinical show that for the cases in order of importance has been Staphylococcus spp (28.8%), Corynebacterium spp (16.5%), and Streptococcus spp (13.1%) and clinical cases characterized as Gram-negative pathogens (23.3%), and Streptococcus spp (18.6%).

Mastite é o principal problema sanitário em uma propriedade leiteira. É um processo infeccioso multifatorial. Está se estudando a dinâmica da infecção em rebanho leiteiro, com visitas mensais por um período de um ano com avaliação da prevalência de casos clínicos e subclínicos, com o objetivo de se estabelecer um programa de controle. Os resultados obtidos até o momento no que se refere à etiologia das mastites mostram que para os casos subclínicos em ordem de importância tem-se Staphylococcus spp (28,8%), Corynebacterium spp (16,5%) e Streptococcus spp (13,1%) e para os casos clínicos os patógenos caracterizados como Gram negativos (23,3%) e Streptococcus spp (18,6%).
Etiology of bovine mastitis in program of control
Keywords: Monitoring; Microbiology; Bovine mastitis; Monitoramento; Microbiologia; Mastite bovina